An Analysis Of The Traditional Treatment Of Jampi-Jampi By Shamans In The Health Practices Of The Indigenous People Of Citorek Village - Maesaroh, Iis; Nurfalah, Siti; Nursyamsiah, Siti; Jamaludin, Ujang (Riwayat: Educational Journal of History and Humanities, 2025)
Traditional medicine heal spells are traditional treatments carried out by shamans and are believed by the indigenous people of Citorek Village to cure various diseases. This research aims to find out the meaning of the traditional healing spells in the Citorek Village indigenous community, to find out the factors that support traditional medicine still existing in the Citorek indigenous community in the current modern era, and to find out the impact of the traditional jampi-jampi treatment in Citorek village. The type of research carried out is descriptive research. Descriptive research is aimed at describing existing phenomena, whether natural or man-made. In this research, interviews were conducted with several indigenous people of Citorek Village as a medium for obtaining research and study data from several literatures such as journals, theses, books and articles. The results of this research show that the indigenous people of Citorek Village interpret this traditional incantation treatment as a treatment that is still full of spiritual power and a form of respect for ancestral heritage. The factors that influence this treatment are still carried out in the modern era, namely due to social and environmental factors, economic factors, and cultural factors that exist in the traditional village of Citorek Village. This traditional incantation treatment has a positive impact on the recovery of patients and does not cause side effects on health because it uses natural ingredients as medicine. Apart from that, the impact of integration between traditional and modern medicine can provide significant benefits for patients. With the right collaboration, these two approaches can work hand in hand to improve the quality of health services in the community.